Determination of drugs of abuse and pharmaceuticals in skeletal tissue by UHPLC–MS/MS. (September 2018) - Orfanidis, Amvrosios; Gika, Helen; Mastrogianni, Orthodoxia; Krokos, Adamantios; Theodoridis, Georgios; Zaggelidou, Eleni; Raikos, Nikolaos
Highlights: The method provides unambiguous identification and quantitative data for drugs in bones. It is a useful tool for toxicological purposes in legal cases. 27 pharmaceuticals, DOA and metabolites can be determined in bone samples. Cocaine, benzoylecgonine, morphine, codeine and bromazepam were found in samples. After 1year burial, these drugs were detectable in both bone and bone marrow. Abstract: In several medico legal cases bone analysis may provide the only source of toxicological information. The present study reports the development of an UHPLC–MS/MS method for the detection and quantification of 27 drugs and pharmaceuticals in human bones. The target compounds comprise pharmaceuticals (antipsychotics and antidepressants) and some of the most important groups of drugs of abuse: opiates, cocaine, cannabinoids, amphetamines and benzodiazepines. Sample pretreatment was studied and the best results were obtained after extraction with methanol, stirring and ultra-sonication. The extract, after filtration, evaporation and reconstitution was analysed on a reversed-phase column (C18) in gradient elution over 17 min. The method was found to be selective, and sensitive offering limits of detection (LOD) from 0.03 to 1.35 ng/g of bone. Validation included evaluation of limit of quantification (LOQ), recovery, carry-over, matrix effect, accuracy and precision (RSD%) of the method. The method performed satisfactory in relation to established bioanalytical criteria and was therefore applied to the analysis of bone and bone marrow obtained post-mortem from chronic drug abusers, offering unambiguous identification and quantitative determination of drugs in bones from legal cases where the analysis of blood was not feasible.